1989
DOI: 10.1016/0035-9203(89)90712-8
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonitis in human visceral leishmaniasis

Abstract: The involvement of the lung in 13 cases of human visceral leishmaniasis was studied. Interstitial pneumonitis with mononuclear cells was found in 76.8% of the cases; 53.8% also had foci of septal fibrosis. Leishmania were seen within macrophages in 3 cases only. However, all 10 interstitial pneumonitis cases showed PAP-positive material using specific L. donovani (MHOM/BR/72/LD 46) antiserum. 3 cases with no interstitial pneumonitis were PAP-negative. A short discussion about clinical aspects and the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
8

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 11 publications
0
36
0
8
Order By: Relevance
“…Interstitial pneumonitis in visceral leishmaniasis was initially described in humans in 1959 3 and later confirmed by other authors 4,6,12,19 . In dogs, pulmonary lesions are very similar to those observed in humans, and were previously characterized by some authors as interstitial pneumonitis mainly characterized by thickening of alveolar walls associated with the presence of a chronic cellular exudate mainly consisting of macrophages 1,23 .…”
Section: Introductionmentioning
confidence: 69%
“…Interstitial pneumonitis in visceral leishmaniasis was initially described in humans in 1959 3 and later confirmed by other authors 4,6,12,19 . In dogs, pulmonary lesions are very similar to those observed in humans, and were previously characterized by some authors as interstitial pneumonitis mainly characterized by thickening of alveolar walls associated with the presence of a chronic cellular exudate mainly consisting of macrophages 1,23 .…”
Section: Introductionmentioning
confidence: 69%
“…The syndrome of antidiuretic hormone secretion in kala-azar patients may be started by interstitial pneumonitis described in 76.8% of necropsied patients 12 . The widespread and intensive inflammatory state involving the lungs, the liver, the kidneys, the intestines and the lymphatic ganglia induced to increase production of plasma prostaglandins and renin 9,29,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…A dry cough is a constant symptom of kala-azar, that persists from the onset of the disease throughout its entire clinical course. The parasitary etiology of the pneumonitis can be confirmed by immunohistochemical reaction using anti-leishmania polyclonal specific anticorps 12 . Lobar pneumonia is a frequent complication of more debilitated patients, when secondary pulmonary bacterial infections occur.…”
Section: Introductionmentioning
confidence: 99%
“…In these other organs, mononuclear cell inflammatory infiltrate appears in the presence of few Leishmania antigens; this appearance suggests that immune mechanisms play a role in lesioning. Studies of lungs have observed multifocal interstitial pneumonitis, a process that is driven by Leishmania antigens 21 and the participation of immune elements. Recently, the inflammatory process constituted by mononuclear cells was characterized, and shown to be constituted by macrophages and CD8 + T cells.…”
Section: Immunopathogeny In Non-lymphoid Organsmentioning
confidence: 99%